Activation of the MyD88 Pathway of Innate Immune Response to Recombinant BCG Malaria Vaccine Candidate: The Role of TLR-4 - Muhammad Adamu Abbas; Rapeah Suppian (UMYU Journal of Microbiology Research)
Malaria, a highly devastating disease caused by Plasmodium spp. puts half the world’s population at risk and has defied the ever-enhanced treatment, control and elimination strategies, necessitating the search for vaccine alternatives. A recombinant BCG (rBCG) expressing the merozoite surface protein 1C (MSP-1C) of Plasmodium falciparum was developed in our laboratory, which exhibited some immunomodulatory effects through undefined mechanisms likely activated by Toll-like receptor-4 (TLR-4). This study tested the hypothesis that TLR-4 mediates the attachment between rBCG and macrophages eliciting an immune response through the myeloid differentiation primary response 88 (MyD88) pathway. In this study, mice (n = 6 per group) were injected with PBS-T80, parent BCG or rBCG in the presence or absence of a TLR-4 inhibitor; TAK- 242 and western blot analysis carried out on the macrophages obtained to determine the role of TLR-4 in the activation of the MyD88. The results obtained showed a significant increase in the expression of the proteins in favour of the rBCG construct compared to the parent BCG and PBS- T80. These increase was significantly inhibited in the presence of TAK-242 signifying the role of TLR-4 in the activation MyD88 pathway of innate immune responses against recombinant BCG malaria vaccine candidate, presenting for the first time an empirical evidence of the importance of TLR-4/macrophage attachment mechanism and its effects as a fore-runner in the MyD88 pathway of immune response to our rBCG expressing the MSP-1C of P. falciparum.